Discoidin domain receptor 2 (DDR2) promotes breast cancer cell metastasis and the mechanism implicates epithelial–mesenchymal transition programme under hypoxia. Issue 4 (15th September 2014) - Ren, Tingting; Zhang, Wei; Liu, Xinping; Zhao, Hu; Zhang, Jian; Zhang, Jing; Li, Xia; Zhang, Yan; Bu, Xin; Shi, Man; Yao, Libo; Su, Jin
Abstract A wide range of genes involved in breast cancer metastasis have been reported to be related to the microenvironment. We studied the role of discoidin domain receptor 2 (DDR2), a collagen‐binding receptor, in breast cancer progression under hypoxic conditions. We showed that DDR2 protein expression closely correlated with the expression of hypoxic marker HIF‐1α in clinical breast cancer specimens. The in vitro data demonstrated that hypoxia treatment increased the levels of both expression and phosphorylation of DDR2 in human breast cancer cell lines. In vivo, orthotopic breast tumour xenografts with DDR2 knockdown displayed reduced dissemination and significant prevention in pulmonary and lymphatic metastasis; conversely, these processes were significantly facilitated by the enforced expression of the activated form of DDR2. Further mechanism studies indicated that DDR2 plays an indispensable role in a series of hypoxia‐induced behaviours of breast cancer cells, including migration, invasion, and epithelial–mesenchymal transition (EMT). The transcription factor Snail was found to mediate DDR2‐induced down‐regulation of the cell–cell adhesion molecule E‐cadherin. It was also documented that there is a correlation between DDR2 and E‐cadherin expression with the presence of lymph node metastases in 160 cases of invasive human breast carcinoma. In addition, we provided evidence that DDR2 silencing in breast cancer cells prevents the hypoxia‐induced activation of ERK MAPK, suggesting its potential involvement in mediating the effect of DDR2 on hypoxia‐induced signalling. Based on the results of this study, we conclude that DDR2 participates in hypoxia‐induced breast cancer metastasis through the regulation of cell migration, invasion, and EMT, and thus may serve as an accessible therapeutic target for the treatment of breast cancer.Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.